Tuberculosis of Gall Bladder - RANDHAWA, A H; ARAIN, G M; RANDHAWA, M H (Annals of King Edward Medical University, 2020)
Tuberculosis of gallbladder is a rare occurrence in the world of medical literature", First case was reported in 1870. Were is presented a case of perforated gallbladder due to tuberculosis because of its rarity.